Architectural Design for Data Security in Cloud-based Big Data Systems (Baghdad Science Journal, 2024)
Architecture design of system is creative process after all. Non-functional requirements and software architecture have a strong relationship. Security of system is one of great concern and it is a non-functional need and requirement. The architectural style and structure chosen for a system should be based on the non-functional system requirements. Big Data technologies are used to store handles huge amounts of operational data in the public domain. Structure and behavior diagrams of the system is proposed that use a secure architectural design for a system that works over the cloud. Different components of Big Data have been investigated in this research work due to the seriousness of security issues focus on privacy and confidentiality. The security of data over the cloud being outsourced is a growing concern. There are outsider and insider malicious database administrators who can gain access and modify private and sensitive data therefore database service provider can be deceitful. Security mechanisms are necessarily required to protect sensitive data residing on public clouds. At the application level, the proposed solution ensures privacy and confidentiality of data at rest over the cloud. Extensive tests have been carried out, and the results of this research work are as follows that the recorded results revealed statistically significant variations in plaintext and multimedia contents (i.e., audio and video) with time measured in milliseconds for small, medium, and large datasets..